Criminal Pathways in the Spanish Detective Novel - Frechilla, Emilio (2024)
In this article we depart from the hypothesis that the crimen novel is understood as a metaphorical journey in search of the truth. To reach its destination, the genre follows a heterogeneous literary trajectory, presented as a plot full of obstacles and narrative turns that conceal a reflection on the surrounding reality. This construction conveys an experience of the reader’s fears and concerns. We concluded that the metaphor of the journey contributes to establishing a new realism that characterizes the Spanish crime novel of the last few decades.